ESTIMASI POTENSI BIOMASSA DAN MASSA KARBON HUTAN TANAMAN Acacia crassicarpa DI LAHAN GAMBUT (Studi Kasus di Areal HTI Kayu Serat di Pelalawan, Propinsi Riau) - Yuniawati; Ahmad Budiaman; Elias (Jurnal Penelitian Hasil Hutan, 2011)
The role of forests as carbon sink and carbon store is undoubtedly important to reduce the carbon amount in the earth atmosphere thereby preventing greenbouse (GHG) effect that can induer the global warming. Among the varisar types of forest, peat swamp forest serves as the largest carbon store. A research bas been carried out at the fiber wond plantation forest comprising mostly Acacia crassicarpa species that grew on a peat land, at the Pelalawan sector, Rian Province. The research was to obtain allometric equatios that related the growth parameters of A. crassicarpa trees (Le tree diameter (D) and height either a total (tot) or branch free (Hbc)) to their growth products Le.biomess (W) and carbon mass (C). It was found that the best fitted and must representative allometric equations were consecutively IF= 0.398918D Hix (for estimating biomass patency) and C = 0.131D Htol""" (for carbon mass potency) Fartbremore, samples A. Crassicarpa tree from different stand ages (2,3,4, and 5 years old) covering particular free portions (Le main stems, branches, twigs, leaves, and roots) were tested for moisture contents, specific growity/density, ash content, volatile matter and fisced carbon. The allometric equations obtained were used to measure and estimate the biomass and carbon mass potencies of A. crassicarpa tree stands at their age group, iz. 2,3,4 and 5 years old Using those allometric equations, the estimates of biomass (W) of A. Crassicarpa for age 2, 3, 4 and 5 years old are 44.98 tons/ha, 70.35 tons/ha, 134.05 tons/ba, and 234.78 tons/year. The potency of carbon mass are 12.09 tons/ha, 36.23 tons/ha, 76.09 tons/ha and 133.10 tons/ha, for stand age 2,3,4 and 5 respectively.